An Evaluation of Metaphorical and Divine Love in Fuzûlî's Leyla and Macnun Epic in the Context of Cost and Reward - Ulucan, Mehmet; Zeren, Erhan (Kütahya Dumlupinar University, 2026)
In classical Turkish poetry, many emotions, thoughts, and situations are evaluated within the context of price and reward. Since every action and every difficulty endured in real life involves a price, there is an expected reward. It is incorrect to expect this price only in this world or only in the afterlife. As the difficulties and hardships encountered on the path to achieving the goal increase, the meaning and satisfaction of the reward obtained or expected at the end of the path/process also increase. Indeed, an easily obtained reward has little value. Therefore, the suffering endured, the difficulties experienced, and the hardships encountered better express the price paid. The heavier, more difficult, and greater the price paid on the path of love, the more important and valuable the reward obtained or expected. The 16th-century poet Fuzûlî, in his mesnevi (narrative poem) Leyla and Majnun, offers various evaluations of love, the lover, and the beloved, attempting to address not only the known and visible dimensions of love but also its unknown and invisible aspects. In his epic poem "Layla and Majnun," Fuzuli expresses his views on the various states of love. In this poem, Fuzuli demonstrates a harmony, order, and balance in his evaluation of the different states and conditions of love. He emphasizes that in love, a privileged state that allows one to transcend oneself, the price and the reward complement each other, and one can substitute for the other.

Klasik Türk şiirinde birçok duygu, düşünce ve durum, bedel-ödül bağlamında değerlendirilmiştir. Gerçek hayatta yapılan her iş ve çekilen her türlü zorluk bir bedelden ibaret olduğu için beklenen bir ödül söz konusudur. Bu bedelin sadece bu dünyada veya sadece öteki dünyada beklenmesi doğru değildir. Hedefe ulaşmak için girilen/gidilen yolda karşılaşılan zorluklar ve sıkıntılar giderek artmakta ise yolun/sürecin sonunda elde edilen veya edilecek olan ödülün anlamı ve verdiği tatmin duygusu da artmaktadır. Nitekim kolayca elde edilen bir ödülün değeri az olur. Bu yüzden çekilen çileler, yaşanan zorluklar ve karşılaşılan sıkıntılar, ödenen bedeli daha iyi ifade etmektedir. Aşk yolunda ödenen her bedel ne denli ağır, zor ve büyük ise elde edilen veya edilmesi beklenen ödül de o denli önemli ve değerli olur. 16. yüzyıl şairi Fuzûlî Leylâ ile Mecnûn adlı mesnevisinde aşk, âşık ve maşuk üzerinden çeşitli değerlendirmelerde bulunmuş, aşkın bilinen ve görünen boyutunun yanında bilinmeyen ve görünmeyen boyutlarına da değinmeye çalışmıştır. Fuzûlî, Leylâ ile Mecnûn adlı mesnevisinde aşkın türlü hallerine dair telakkilerini dile getirmiştir. Fuzûlî’nin bu mesnevisindeki aşkın çeşitli hal ve şartlarının değerlendirilmesinde bir uyum, düzen ve dengenin gözetildiği görülmektedir. İnsanın kendini aşmasını sağlayan ve ayrıcalıklı bir hâl olan aşkta; bedel ve ödülün birbirini tamamladığı, birinin diğerinin yerine geçebildiğinin üzerinde durulmaya çalışılmıştır.
Fuzûlî’nin Leylâ ile Mecnûn Mesnevisindeki Aşkın Bedel-Ödül Bağlamında Değerlendirilmesi
Keywords: Classical Turkish Literature of Ottoman Field; Osmanlı Sahası Klasik Türk Edebiyatı